MicroRNA-196a in human adipose tissue - Hilton, C (2015)
MicroRNAs are small non-coding RNAs that have been shown to play a role in adipose tissue biology. Adipose tissue depots differ in terms of the metabolic risk that they confer. Therefore, I aimed to identify microRNAs which regulate body fat distribution. An initial microarray screen of abdominal subcutaneous and gluteal adipose tissue, with validatory qPCR, identified microRNA-196a as being more highly expressed in gluteal adipose tissue. These expression patterns were retained in primary and immortalised pre-adipocytes from abdominal subcutaneous and gluteal adipose tissue. The precursor of miR-196a contains a single nucleotide polymorphism, rs11614913. Genotyping was performed on 5,823 individuals from the Oxford Biobank and combined with detailed information on body composition by DXA scanning and miR-196a expression determination in fat biopsies. This revealed that the rs11614913 TT genotype was associated with a 32% reduction in miR-196a expression in abdominal subcutaneous adipose tissue (p=0.002), an expansion in waist-to-hip ratio and an increase in mean adipocyte size in abdominal subcutaneous adipose tissue in males. RS11614913 was also found to be associated with bone mineral density, and the relationship between bone mineral density and body fat distribution was explored using the Oxford Biobank. To establish a functional role for miR-196a, the Pt2 abdominal and gluteal cell lines were validated as models for pre-adipocyte proliferation and adipogenesis. MiR-196aKO pre-adipocyte cell lines were generated. MiR-196aKO was found to reduce proliferation in abdominal subcutaneous (p=0.002) and gluteal (p=0.002) pre-adipocytes, with no effect in adipogenesis. In addition, transcriptomic profiling of miR-196aKO pre-adipocytes revealed enrichment for GO term clusters related to extracellular matrix and angiogenesis, suggesting a mechanism by which miR-196a might regulate regional adipose tissue expansion.